2015
DOI: 10.1007/s12369-015-0298-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Engagement with Social Robots

Abstract: To interact and cooperate with humans in their daily-life activities, robots should exhibit humanlike "intelligence". This skill will substantially emerge from the interconnection of all the algorithms used to ensure cognitive and interaction capabilities. While new robotics technologies allow us to extend such abilities, their evaluation for social interaction is still challenging. The quality of a human-robot interaction can not be reduced to the evaluation of the employed algorithms: we should integrate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
158
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 171 publications
(181 citation statements)
references
References 68 publications
0
158
0
1
Order By: Relevance
“…The automatic detection of engagement using multi-modal cues has been investigated in the field of Human Robot Interaction (HRI) and Social Signal Processing (SSP) [35,38,4]. In [29], hand-coded features such as speech, gaze, gesture, and postures of two children were utilised to model individual and grouplevel engagement.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…The automatic detection of engagement using multi-modal cues has been investigated in the field of Human Robot Interaction (HRI) and Social Signal Processing (SSP) [35,38,4]. In [29], hand-coded features such as speech, gaze, gesture, and postures of two children were utilised to model individual and grouplevel engagement.…”
Section: Related Workmentioning
confidence: 99%
“…While the HRI studies [4,29] revealed that gaze-oriented movements and hand gestures were related to engagement, the settings often had regulations on behaviours of subjects or relied on hand-coded features. Without any regulation, the automatic extraction of these features is limited in naturalistic settings.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations